The importance of developing foreign trade to achieve economic growth in Algeria during the period (1991-2017) using the ARDL model - Nawel BOUKLIA (المجلة الدولية للأداء الاقتصادي, 2021)
This study aims to identify the foreign trade and its impact on economic growth in Algeria for the period (1991-2017). The results indicate that there is a positive relationship between exports and economic growth. Thus, the result of study recommends the need to encourage and develop the non-oil sectors, as it is exposed to risk due to the volatility of their prices. Therefore, it calls for the elimination of the unilateral sector .